Transcriptome analysis provides new insights into the response of canine intestinal epithelial cells treated by sulforaphane: a natural product of cruciferous origin - Li, Kaiqi; Yan, Jin; Wang, Shiqi; Zhu, Chuyang; Zhu, Qi; Lu, Sichen; Hu, Ping; Dessie, Tadelle; Kim, In Ho; Ahmed, Abdelkareem A.; Liu, Hao-Yu; Ennab, Wael; et al. (Frontiers in Veterinary Science, 2024)
This study presents a comprehensive transcriptome analysis of canine intestinal epithelial cells following treatment with sulforaphane (SFN), a naturally occurring compound found in cruciferous vegetables with established anti-inflammatory and antioxidant properties. Through high-throughput sequencing, we identified 29,993 genes, among which 1,612 were differentially expressed, with 792 up-regulated and 820 down-regulated in response to SFN treatment. Our analysis revealed significant enrichment of genes in pathways associated with the inflammatory response, lipid metabolism, oxidative stress response, and T-cell mediated immunity, suggesting SFN’s potential in modulating these biological processes. Notably, the PPARγ gene, which plays a crucial role in the body’s oxidative stress and inflammatory response, was highly up-regulated, indicating its possible centrality in SFN’s effects. Gene–gene interaction analysis further supported SFN’s role in alleviating inflammation through PPARγ, with key genes in oxidative stress and inflammatory response pathways showing significant correlations with PPARγ. Overall, our findings provide molecular evidence for SFN’s protective effects on canine intestinal health, potentially through the modulation of inflammatory and oxidative stress pathways, with PPARγ emerging as a critical mediator.